KAFIR DALAM AL-QUR’AN - Muhaemin Muhaemin (SUHUF, 2021)
This paper discusses the view of Mahmud Yunus concerning the meaning of ‘kafir’ in Tafsir Al-Qur’an Al-Karim. By using library research and using descriptive-analytic data processing, it becomes clear that the socio-historical context has a great influence on Mahmud Yunus in understanding the text of the Qur’an, especially with regard to the meaning of kafir. Mahmud Yunus interprets infidels by looking at the behavior and daily life of the Indonesian people. For example, when interpreting surah an-Nahl/16: 112 he says a disbeliever is anyone who does not thank Allah. He contexts this verse with rich countries that have rubber plantations in Indonesia. For not thanking Allah, the punishment Allah sent down was in the form of a decrease in the selling price of rubber. In another verse of Surah at-Taubah/9:107 what is called by infidel, namely those who build a mosque with the intention of dividing the people. Different from other scholars, in interpreting the Qur’an Mahmud Yunus put aside the history of the word infidel of the pre-Islamic era. On the other hand, the subjectivity related to the meaning of the word infidel is also seen in his interpretation.